Law and justice in community - Barden, Garrett; Murphy, Tim, 1967- (Oxford : Oxford University Press, 2010)
This title refutes modern, positivist theories of the nature of law and argues that law exists in all human communities before it is formally expressed. Drawing on anthropology and classical theory, the theory offered will be of interest to students of philosophy, anthropology, and the sociological study of law.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Law -- Philosophy; Justice -- Philosophy; Sociological jurisprudence; Social structure; Community life